Freudian Theory and Consciousness: A Conceptual Analysis** - De Sousa, Avinash (Medknow Publications, 2011)
This paper aims at taking a fresh look at Freudian psychoanalytical theory from a modern perspective. Freudian psychology is a science based on the unconscious (id) and the conscious (ego). Various aspects of Freudian thinking are examined from a modern perspective and the relevance of the psychoanalytical theory of consciousness is projected. Do psychoanalysis and the unconsciousness have something to teach us about consciousness? Approaching Freud from a historical, psychoanalytical, anthropological and sociological perspective, we need to look at how Freudian theory may contribute to a better understanding of consciousness. We also need to look at psychoanalytical psychotherapy and its contribution to a better understanding of body-mind dualism and consciousness as a whole. Ego psychology is considered in the present day context and it is synthesized with various psychological studies to give us a better understanding of consciousness.